Avaliação dos efeitos toxicológicos da associação dos herbicidas 2,4-D e Piclo- ram em peixes da espécie Colossoma macropomum (CUVIER, 1818) - LISBÔA, João David Batista (Universidade Federal do Oeste do Pará, 2021)
Pesticides are active ingredients, with a high degree of proven toxicity, can cause morphophysiological changes and even mortality of organisms. There are studies showing their damage to water, soil, insects, crustaceans, amphibians and fish due to direct exposure, at the time of application, or indirect, by residues that remain in the environment. Herbicides are the main pesticides detected in surface and ground water. Picloram and 2,4-D are examples of these herbicides that can remain in the environment for years. Due to its commercial formulation is accessible and affordable, the population can easily purchase individually or in combination. Despite there are many studies with these active ingredients, it has not been possible to clarify their mechanisms of action in organisms, except in plants. Thus, the proportion of environmental and human hazards is unknown. This study contains 3 chapters: the first deals with a descriptive review of the literature on ecotoxicology, pesticides and biomarkers and a scientometric analysis of the use of Colossoma macropomum in toxicological studies. The second article evaluates the acute toxicity of the association of the 2,4-D and Picloram herbicides in Colossoma macropomum. And the third evaluates the behavioral and histological changes in fish of the species Colossoma macropomum exposed by association of the herbicides 2,4-D and Picloram. The experiments performed in this study were approved by CEUA/UFOPA, under protocol No. 0120190053, and followed international guidelines for the assessment of acute sensitivity and toxicity of USEPA No. 850.1075/2006 and OECD No. 203/1992. The fish of the species Colossoma macropomum have been shown to be emerging test organisms in toxicological studies mainly in Brazil, as observed through the scientometric analysis. Through sensitivity tests, the species confirmed their usability for toxicity testing and environmental biomonitoring. Thus, Colossoma macropomum was evaluated at five different concentrations (3.5, 5, 6, 7, 8 mg / L) of the commercial formulation of 2,4-D and Picloram in a static system, estimating the LC50- 96h at 5.54 mg/L by Trimmed Spearman-Karber method. The behavioral parameters were evaluated by video recording at 0, 2, 4, 6, 8, 12, 24, 48, 72 and 96 hours after exposure. Histological analysis was performed on the gills and liver of fish stained with hematoxylin and eosin. The behavioral changes evaluated were excitatory swimming, stay in the upper zone, surface breathing, loss of balance, erratic swimming, spasm and paralysis. The histological changes in the gills were hyperplasia and lamella 10 degeneration, and in the liver, intercellular vacuolization. Therefore, the results demonstrated that Colossoma macropomum is a potential organism for biomonitoring toxicological studies. Its exposure to the herbicides Picloram and 2,4-D showed several behavioral and histological changes, proving their risks to the environment, including humans who live near the plantations that use this pesticide.